Dijkstra, Lewis, Maseland, Jos (eds. y coords.) (2016): The State of European Cities 2016. Cities leading the way to a better future. Brussels, European Union, United Nations Human Settlements Programme (UN-Habitat), 214 pp. isbn (Volume): 978-92-1-132717 - García Ferrero, Alejandro (Espacio Tiempo y Forma. Serie VI, Geografía, 2017)
Reseña de: Dijkstra, Lewis, Maseland, Jos (eds. y coords.) (2016): The State of European Cities 2016. Cities leading the way to a better future. Brussels, European Union, United Nations Human Settlements Programme (UN-Habitat), 214 pp. isbn (Volume): 978-92-1-132717-5.